Impacts of Activation of the Mitogen-Activated Protein Kinase Pathway in Pancreatic Cancer - Furukawa, Toru (Frontiers in Oncology, 2015)
Pancreatic cancer is characterized by constitutive activation of the mitogen-activated protein kinase (MAPK) pathway. Mutations of KRAS or BRAF and epigenetic abrogation of DUSP6 contribute synergistically to the constitutive activation of MAPK. Active MAPK induces the expression of a variety of genes that are thought to play roles in malignant phenotypes of pancreatic cancer. By blocking the functions of such induced genes, it is possible to attenuate malignant phenotypes. The development of drugs targeting genes downstream of MAPK may provide a novel therapeutic option for pancreatic cancer.